Evaluation under real-life conditions of a lifestyle intervention for diabetes prevention developed by the municipal health services of Madrid, Spain - Carmen Martin-Ridaura; Darío Ochoa-Esteban; Carmen Berlinches-Zapero; Dolores Ruiz-Fernández; Vanessa Sanz-Martín; Rosario Gavira-Izquierdo; Sebastià March; María López-Toribio; Mercedes Ceinos-Arcones; The ALAS Project Working Group (Scientific Reports, 2022)
Abstract The Diet, Physical Activity and Health (Alimentación, Actividad física y Salud, ALAS) program is an intervention implemented by the municipal health services of Madrid with the objective of reducing weight and preventing diabetes in high-risk population by improving diet and physical activity. The ALAS program combines individual visits with a 10-session group workshop that takes place over a 6-month period. This study evaluated the effectiveness of the ALAS intervention implemented under real-life conditions between 2016 and 2019. The intervention was evaluated with a pre- and post-intervention study with follow-up performed 6 and 12 months from the start of the program. The analyzed outcomes were a 5–10% reduction in the initial weight, body mass index (BMI), waist circumference and a change in glycemic status in prediabetic participants. Statistical models were adjusted by sociodemographic variables. The participants were recruited from municipal community health centers or referred by municipal occupational health services. Between 2016 and 2019, 1629 people participated in the program. At 6 months, 85% of the participants had lost weight; 43% had lost 5% or more of their initial weight, and 12% had lost 10% or more. Regarding BMI, 22.3% of participants who were initially obese were no longer obese, and 15.2% of the overweight participants achieved normal weight. A total of 35.1% of the prediabetic participants reverted to normoglycemic status. The intervention was found to be more effective for men, for those who completed the intervention and those who accessed the program through the occupational health route. Among the participants who accessed the intervention via the community, the intervention was more effective in those with a high educational level. The evaluation demonstrated the effectiveness of the ALAS program for reducing weight and the risk of developing Type 2 diabetes when applied under real-life conditions. The effectiveness of the intervention differed according to gender, access route and educational level of the participants.